2000
DOI: 10.1042/cs20000039
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balloon mitral valvuloplasty on systemic and regional left atrial levels of prothrombin fragment 1+2 in mitral stenosis

Abstract: A proportion of mitral stenosis patients with left atrial spontaneous echo contrast but without thrombus exhibit a regional hypercoagulable state, characterized by increased left atrial levels, but normal venous levels, of prothrombin fragment 1+2 (F1+2), a marker of thrombin generation. Valve dilatation by balloon mitral valvuloplasty has beneficial effects on left atrial spontaneous echo contrast, but its effect on left atrial thrombin generation is unknown. We examined the effects of balloon mitral valvulop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
3
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
3
1
Order By: Relevance
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
contrasting
confidence: 99%
See 3 more Smart Citations
“…Contrary to the assertion of Li-Saw-Hee and Lip that thrombogenesis in cardiac disease is likely to be a generalized process, we believe that there is now abundant evidence from our group [1][2][3][4] and others [5][6][7] which supports the existence of a localized increase in left atrial coagulation activity in mitral stenosis. Moreover, this coagulation activation is not primarily due to atrial fibrillation as it is also observed in patients with sinus rhythm who have left atrial spontaneous echo contrast [1,7].…”
contrasting
confidence: 99%
“…However, a feature of our study design was to only include patients without any prolongation of their INR at the beginning of the procedure [4]. While this does not completely exclude a residual effect of warfarin in our study, our previous finding of no difference in venous or left atrial F1j2 levels between patients who had or had not been on warfarin prior to the valvuloplasty procedure [1], suggests that any such effect was likely to have been small.…”
mentioning
confidence: 96%
See 2 more Smart Citations